The Relationship Between Dietary Patterns And The Incidence Of Diabetes Mellitus At The Pereumeu Public Health Center, West Aceh Regency In 2026 - Muhammad Khalid Khalid; Alya Farha; Jauda Lotvia; Nailatul Mona Okfalia; Nusti Cinta Hasmika; Tiarnida Nababan (International Journal of Health Engineering and Technology, 2026)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by increased blood glucose levels due to impaired insulin secretion. One of the main modifiable risk factors is an unhealthy diet. In the working area of the Pereumeu Community Health Center, West Aceh Regency, the number of DM patient visits shows a fluctuating but still significant trend every year. To determine the relationship between diet and the incidence of Diabetes Mellitus at the Pereumeu Community Health Center, West Aceh Regency in 2026. Quantitative research with a correlational design using a cross-sectional approach. The study was conducted in March-April 2026 with a population of patients who checked themselves. The research sample was obtained as many as 42 respondents selected using a purposive sampling technique. Data collection was carried out using a diet questionnaire and an observation sheet for blood glucose laboratory results. Data analysis used descriptive analysis for univariate and the Chi-Square test for bivariate (p = 0.05). The results of univariate analysis showed that the majority of respondents were male (61.9%), worked as self-employed (52.4%), had a good diet as many as 26 respondents (61.9%), and respondents who did not experience DM as many as 26 people (61.9%). The results of the Chi-Square bivariate test showed a p-value = 0.001 (p <0.05), which means there is a statistically significant relationship between diet and the incidence of Diabetes Mellitus. Diet has a significant relationship with the incidence of Diabetes Mellitus at the Pereumeu Community Health Center. It is hoped that health agencies will improve healthy diet management education programs for local communities in order to reduce the mortality rate of DM.